Representation of Traumatic Memory in the Film Drishyam: A Barthesian Reading - Srilekha B. P.; V. Bharathi Harishankar (IAFOR Journal of Arts & Humanities)
Cinema has long served as a vital medium for disseminating information and knowledge in modern society. Its portrayal of diverse emotions and themes often mirrors societal events in a realistic and compelling manner. Enhanced by various cinematographic techniques, the depiction of trauma is magnified within the visual narrative. This article employs “Drishyam”, a Malayalam film presented in two parts, to analyze the impact of trauma stemming from a singular event. It explores the process of trauma across different phases and examines its repercussions on the individual, family, and local community. The theoretical frameworks of Camera Lucida and Camera Obscura, as proposed by Roland Barthes, provide a basis for interpretation, allowing for the cinematic narrative to be examined from multiple perspectives, as well as highlighting the directorial intent. In particular, this study utilizes Barthes’ concepts of “studium” and “punctum” to evaluate the emotional response elicited from the audience.